(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
This article presents the reduction of nitrite and nitrate content in the soil and food crops by safe and non-toxic fertilizing of agricultural crops through various methods of storage and neutralization of manure released by farm animals.